BRIDGING THE IMMUNOGENICITY OF A TETRAVALENT DENGUE VACCINE CANDIDATE (TAK-003) FROM CHILDREN AND ADOLESCENTS TO ADULTS - C. Halim; V. Tricou; F. Nordio; N. Folschweiller (International Journal of Infectious Diseases, 2023)
Intro: Dengue efficacy studies are not feasible in dengue non-endemic countries. For TAK-003, we present an immunobridging analysis to infer vaccine efficacy as determined in the DEN-301 phase 3 efficacy trial conducted in children and adolescents from eight dengue-endemic countries to adults from non-endemic areas of the USA enrolled in the phase 3 immunogenicity DEN-304 trial. Methods: Children and adolescents aged 4–16 years received two doses of TAK-003 or placebo at Months 0 and 3 in DEN-301 (NCT02747927). In DEN-304 (NCT03423173), adults aged 18–60 years received two doses of TAK-003 or placebo at Months 0 and 3. Geometric mean titers (GMTs) of dengue-neutralizing antibodies were assessed via a validated microneutralization assay; a comparison of GMTs showed non-inferiority for individual serotypes if the upper bound of the 95% CI for the geometric mean ratio (GMR) between the two groups was <2.0. Seropositivity rate was defined as the proportion of participants with post-vaccination reciprocal MNT50 titers ≥10. Findings: Overall, 1,081 baseline-seronegative participants were included in this analysis (702 children/adolescents and 379 adults). At Month 4, noninferiority of immunogenicity was shown for dengue virus (DENV)-1, -2, and -4, but marginally missed for DENV-3 with a GMR (95% CI) of 1.77 (1.53, 2.04) (GMT [95% CI]: adults, 128.9 [115.0, 144.4]; children/adolescents, 228.0 [209.2, 248.5]). By Month 9, non-inferiority was shown for all four serotypes. Seropositivity rates against individual serotypes ranged from 92% to 100% at Months 4 and 9. Similar levels of response were also observed in a number of additional exploratory assessments of the humoral immune response. Conclusion: The analysis shows comparable immune response to TAK-003 in baseline-seronegative adults as in children/adolescents, supporting extrapolation of the efficacy profile of TAK-003 to adults.